(untitled) (Texas Journal of Medical Science, 2022)
In this article, gastrointestinal motility under condition of hypokinesia was studied during experiments. X-ray contrast examinations with barium sulfate showed that passage in the digestive tract slowed down due to changes in gastrointestinal evacuation activity under hypokinesia.